FACTORS INFLUENCING STUDENTS' INTEREST IN LEARNING ENGLISH. - Safira Istiqa; Eni Rosnija; Yanti Sri Rezeki (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbatractThe purpose of this research is to describe the factors influencing of students' interest in learning English and to describe the dominant factors that influence students' interest in learning English on the tenth grade students of Madrasah Aliyah Negeri 1 Sambas in the academic year 2020/2021. The research method used is descriptive research in the form of quantitative research. This research used 31 questionnaires to collect the data. The research subject for this research are tenth grade students that consist of 40 students at Madrasah Aliyah Negeri 1 Sambas in the academic year 2020/2021. The results of the research shows that the factor influencing students' interest in learning English is the external factor with the amount of percentage 70.262% with rating percentage interpretation criteria is middle. From the list of the recapitulating the percentage of each indicator, the dominant factors that influence students' interest in learning English is school factor with percentage 68.99%. Therefore, from the research there are a number of external factors such as teacher, learning facility, learning method, and also school environment that influencing students' interest in learning English. Keywords : InterestLearning EnglishStudents' Interest